Changes of Paradigms in the Life Sciences - Koj, Aleksander (Theoria et Historia Scientiarum, 2007)
Among both laymen and active scientists an opinion prevails that the development of science occurs predominantly by the accumulation of knowledge and a gradual improvement in the picture of nature due to the application of new methods and techniques. The breakthroughs, such as the Big Bang theory in cosmology or deciphering of the Biological Code in the life sciences, are treated as rare exceptions. However, a closer scrutiny of almost any scientific discipline points to a noncontinuous process of development and the appearance of paradigms which are constantly subjected to verification as postulated by Kuhn (1970) in the original theory of „scentific revolutions”.